The Use of Slide Show PowerPoint to Increase Students’ Reading Comprehension Using Narrative Text at Grade V of SDN Pertiwi 070 Sungai Penuh, Academic Year 2025/2026 - Al Padli; Sukarta Kartawijaya; Suci Marselina (The Future of Education Journal, 2026)
This research was a classroom action research, it was done at grade 5th of SD N Pertiwi 070 Sungai Penuh academic year 2025/2026. The aim of the research was to know whether the use power point slide show to improve the students’ reading comprehension by using narrative text, and to know the factors improved the student’ reading comprehension. This classroom action research was conducted in two cycles, each cycle consisted four steps namely planning, action, observation and reflection or evaluation. There were three meetings did in each cycle so there were six meetings during the research. Based on the result of two cycles done in this research, it was found some improvements during the teaching and learning process. There were some improvements they were: the students’ reading comprehension. It was proved by the students’ reading score from each cycle, there were some improvements in cycle one and cycle two. In cycle one the mean score was 54. 54% and it was increased 19.77%. The mean score of cycle two was 74. 31%. The improvements were also influenced by several factors that were classroom activity, classroom management, media and teaching way. Based on the findings and discussion, it could be concluded that the use power point slide show could improve the students’ reading comprehension by using narrative text at grade 5th of SD N Pertiwi 070 Sungai Penuh academic year 2025/2026.